Pengaruh Merger Dan Akuisisi Terhadap Kinerja Keuangan Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (Studi Pada Perusahaan Sektor Energi) - Berliani Agustina; Fahmi Roy Dalimunthe; Ali Sadikin (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
This study aims to evaluate the differences in companies' financial performance before and after mergers and acquisitions. The assessment of financial performance was carried out using several financial ratios, including current ratio, debt to equity ratio, return on equity, return on assets, and net profit margin. The population of this study includes all energy sector companies listed on the Indonesia Stock Exchange (IDX) that engaged in mergers and acquisitions during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in 9 companies that met the criteria. Data analysis was conducted using the paired sample t-test with the help of SPSS version 21. The results indicate that there were no significant differences in the CR, DER, ROE, and ROA ratios before and after the mergers and acquisitions. However, the NPM ratio showed a significant difference between one year before and one year after the merger and acquisition activities